2015
DOI: 10.18632/oncotarget.3341
|View full text |Cite
|
Sign up to set email alerts
|

miR-188-5p inhibits tumour growth and metastasis in prostate cancer by repressing LAPTM4B expression

Abstract: Elucidation of the molecular targets and pathways regulated by the tumour-suppressive miRNAs can shed light on the oncogenic and metastatic processes in prostate cancer (PCa). Using miRNA profiling analysis, we find that miR-188-5p was significantly down-regulated in metastatic PCa. Down-regulation of miR-188-5p is an independent prognostic factor for poor overall and biochemical recurrence-free survival. Restoration of miR-188-5p in PCa cells (PC-3 and LNCaP) significantly suppresses proliferation, migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
88
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 45 publications
8
88
1
Order By: Relevance
“…Decreased expression of miR-188-5p is associated with poor prognosis in patients with PCa, which strongly suggests a potential role of miR-188-5p in suppression of PCa. 38 In summary, our findings are the first to show an association between LAPTM4B polymorphism and risk of PCa in a sample of the Iranian population. Further studies with larger sample sizes and different ethnicities are required to validate our findings.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Decreased expression of miR-188-5p is associated with poor prognosis in patients with PCa, which strongly suggests a potential role of miR-188-5p in suppression of PCa. 38 In summary, our findings are the first to show an association between LAPTM4B polymorphism and risk of PCa in a sample of the Iranian population. Further studies with larger sample sizes and different ethnicities are required to validate our findings.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that miR-188-5p, which acts as a tumor suppressor, inhibits PCa cell proliferation, invasion, and migration through downregulation of LAPTM4B by directly binding to its 3 0 -UTR 38 and subsequent inhibition of the PI3K/AKT signaling pathway. Decreased expression of miR-188-5p is associated with poor prognosis in patients with PCa, which strongly suggests a potential role of miR-188-5p in suppression of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 11 miRNAs have never been studied in liver cancer (Table III). Among the 11 differentially dysregulated miRNAs, the function of miR-374a, miR-188-5p, miR-1183, miR-454, miR-324-3p, miR-484, miR-3188, and miR-216b have been studied in human cancers (27,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43); however, the exact function of miR-4271, miR-1471 and miR-3610 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that miR-1183 and miR-188-5p may represent specific predictors of response to chemoradiotherapy in rectal cancer (32). miR-188-5p is involved in the process of prostate cancer by regulating lysosomal protein transmembrane 4 β (LAPTM4B) (33). The downregulation of miR-188-5p is an independent prognostic factor for poor overall and biochemical recurrence-free survival rates, restoration of miR-188-5p in prostate cancer (PCa) cells significantly suppresses proliferation, migration and invasion in vitro and inhibits tumor growth and metastasis in vivo (33); Overexpression of miR-188-5p in PC-3 cells may significantly enhance the chemosensitivity of the cells to adriamycin (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation